Kontestasi Diskursus Ketahanan Pangan Keluarga - Kakisina, Leunard Onisivorus (CV. Publikasi Indonesia, 2022)
This study examines the contestation of food security discourses between actors in farming families in North Tanimbar District, Tanimbar Islands Regency. This research was conducted in North Tanimbar District, Tanimbar Islands Regency, Maluku Province in January-February 2022. This study used a qualitative research design using a constructivist paradigm. The results showed that there are three main actors in the discourse of food security, namely the government, community, and business actors. Each actor seeks to practice their discourse on farming families. When practicing discourse, there is a discourse interaction between actors that is synergistic. However, the most dominant discourse practiced by families is the community discourse, while the government discourse is a compliment and the business actors' discourse is a driver. The novelty of the research results of the contestation of family food security discourses found at the study site is the rationality and synergy efforts of family farmers in meeting family food needs.